Monoaminergic and Opioidergic Modulation of Brainstem Circuits: New Insights Into the Clinical Challenges of Pain Treatment? - Tavares, Isaura; Costa-Pereira, José Tiago; Martins, Isabel (Frontiers in Pain Research, 2021)
The treatment of neuropathic pain remains a clinical challenge. Analgesic drugs and antidepressants are frequently ineffective, and opioids may induce side-effects, including hyperalgesia. Recent results on brainstem pain modulatory circuits may explain those clinical challenges. A dual action of noradrenergic modulation was demonstrated in animal models of neuropathic pain. Besides the well-established antinociception due to spinal effects, the noradrenergic system may induce pronociception by directly acting brainstem pain modulatory circuits, namely at the locus coeruleus and medullary dorsal reticular nucleus (DRt). The serotoninergic system also has a dual action depending on the targeted spinal receptor, with an exacerbated activity of the excitatory 5-HT3 receptors in neuropathic pain models. Opioids are involved in the modulation of descending modulatory circuits. During neuropathic pain, the opioidergic modulation of brainstem pain control areas is altered, with enhanced local opioid release along with reduced expression and desensitization of µ-opioid receptors (MOR). In the DRt, the installation of neuropathic pain increases the levels of enkephalins and induces desensitization of MOR, which may enhance descending facilitation from the DRt and impact on the efficacy of exogenous opioids. Overall, the data discussed in this review indicate a high plasticity of brainstem pain control circuits involving monoaminergic and opioidergic control. The data from studies of these neurochemical systems in neuropathic models indicates the importance of designing drugs that target multiple neurochemical systems, namely maximizing the antinociceptive effects of antidepressants that inhibit the reuptake of serotonin and noradrenaline and preventing desensitization and tolerance of MOR at the brainstem.